Species Variety, Antibiotic Susceptibility Patterns and Prevalence of Enterotoxin Genes in Staphylococci Isolated from Foodstuff in Central Iran - Laleh HOVEIDA; Behrooz ATAEI; Nour AMIRMOZAFARI; Zahra NOORMOHAMMADI (Tehran University of Medical Sciences, 2020)
Background: The presence and diversity of Staphylococcus species and their enterotoxin-encoding genes in foodstuffs have not been comprehensively studied in some developing countries. This study aimed to assess the frequency of Staphylococcus spp. and their related virulence factors in foodstuffs in Isfahan, Iran. Methods: Overall, 139 foodstuff samples, collected from Isfahan City (center of Iran) from Sep 2015 to Oct 2016, were processed for the presence of Staphylococcus spp. using standard bacteriological procedures and sequence analysis of 16S rRNA gene. Antimicrobial susceptibilities and prevalence of mecA and toxin-encoded genes (sea, seb, sed, see and tsst1) were tested for all of the Staphylococcal isolates. Results: Forty-four Gram-positive cocci were recovered from 139 dairy and meat samples. The most prevalent species were S. vitulinus 25.0% (11/44) and S. aureus 20.5% (9/44); respectively. The most prevalent antimicrobial resistance was noted towards penicillin, cefoxitin and tetracycline. The sec, sea, see and tsst1 genes were found in 19%, 9.5%, 3.5%, and 3.5% of the isolates, respectively. Conclusion: Numerous virulence factors were detected in different Staphylococcus spp. isolated from foodstuffs, more attention should be paid to the presence of the bacteria. Proper hygienic and management practices should be considered in order to increase food safety and prevent extra treatment costs.